Clinical Efficacy And Safety Of Baricitinib In Juvenile Idiopathic Arthritis: A Systematic Review And Meta-Analysis Of Randomized And Observational Evidence - Dr. Varnit Kaushik; Dr. Aqeel Haider; Dr. Prachi Jain; Dr. Jivesh Garg (PAIN, JOINTS, SPINE, 2026)
Background: Baricitinib is an oral selective Janus kinase 1/2 inhibitor that has recently been evaluated in paediatric juvenile idiopathic arthritis (JIA), a heterogeneous chronic inflammatory disease which merits durable arthritis therapy, flare prevention, maintenance and careful surveillance to ensure safety. This systematic review and meta-analysis comprised randomized, open-label, observational, registry and mechanistic evidence regarding the clinical efficacy and safety of baricitinib in JIA.Methods: The search was conducted during the time period of database inception through 2026-06-28 in PubMed/MEDLINE, Embase, Scopus, Web of Science, PsycINFO, Cochrane CENTRAL, ClinicalTrials.gov, WHO ICTRP, EMA, and sources of health technology assessment. Language restrictions were not imposed. Two independent reviewers, with third-reviewer adjudication, conducted thorough information screening, extraction, and risk assessment bias in these publications. Outcomes were disease flare, JIA-ACR response, inactive disease, uveitis response, adverse events, infections, serious adverse events, thromboembolic events, malignancy, and discontinuation. We synthesized random effects (DerSimonian-Laird with REML sensitivity); pooling was performed only if clinical and statistical justification justified it.Results: We reviewed four eligible evidence records: one pivotal randomized withdrawal phase 3 trial, one monocentric case series, one open-label active-controlled uveitis trial, and one post-hoc biomarker analysis. The pivotal trial was the only strong comparative estimate of arthritis efficacy. Baricitinib significantly reduced the risk of a flare among randomized withdrawal subjects when compared with placebo. Crude flare odds also favored baricitinib. Treatment-emergent infections were numerically more frequent during baricitinib continuation than placebo withdrawal, whereas serious adverse events were uncommon in the accessible aggregate data. The uveitis trial failed the prespecified Bayesian primary endpoint. Biomarker findings were hypothesis-generating.Discussion: Evidence supports baricitinib as an effective oral option for selected children and adolescents with active non-systemic JIA after inadequate response or intolerance to cs/bDMARDs, but certainty is limited by responder-enriched randomized withdrawal design, sparse independent replication, small observational samples, and limited long-term paediatric safety data.Conclusion: Baricitinib appears efficacious for flare prevention in selected JIA populations, with an acceptable short-term safety profile. Larger real-world cohorts and long-term registries are needed.